Annual Settlement of Melter & Refiner’s Account since 1860 - Booth, James Curtis
Account Statement listing totals for standard ounces of gold melted, actual wastage, and ratio of wasted to melted for the years 1861-1886.
Keywords: Gold; Smelting; Metals--Refining; Mint of the United States; Metallurgy; Precious metals--Refining; Gold--Refining; Booth, James Curtis, 1810-1888; United States Mint